POTENSI DAN STATUS KERUSAKAN TANAH UNTUK PRODUKSI BIOMASSA DI KABUPATEN KUTAI TIMUR (Studi Kasus Kecamatan Long Masangat, Batu Ampar dan Rantau Pulung) - Muli Edwin; Harmi Suptrapti; Iin Sumbada Sulistyorini; Aliri Aliri (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Soil degradation to support the growth and development of plants and produce goods and services has become a global concern. To support government programs and efforts to improve land, the role and cooperation of researchers with local governments should be increased to multiply, and information related to the potential of soil degradation can be used as supporting data for development planning in an area. The potential and status of soil degradation in the region of East Kutai Regency, are still relatively low. But it has a high potential for damage because land use more increasing for various purposes. Soils in East Kalimantan is dominated by old soil, such as Podsolic or Ultisols, easily damaged if utilized without regard to principles of conservation. Especially for soil in Rantau Pulung there is a parameter with exceeded status of standard quality, i.e. permeability; then in Batu Ampar found four parameters, namely permeability, the composition of soil fraction, bulk density and soil pH, next to Long Masangat founded two parameters, namely bulk density and permeability. The more of limiting factors, then in the land use should also apply and demand high conservation treatment to maintain the land or soil quality.